A community approach for pathogens and their arthropod vectors (ticks and fleas) in cats of sub-Saharan Africa - Madder, Maxime; Day, Michael; Schunack, Bettina; Fourie, Josephus; Labuschange, Michel; van der Westhuizen, Wouter; Johnson, Sherry; Githigia, Samuel Maina; Akande, Foluke Adedayo; Nzalawahe, Jahashi Saidi; Tayebwa, Dickson Stuart; Aschenborn, Ortwin; et al. (Bmc, 2022)
Background: Arthropod-borne pathogens and their vectors are present throughout Africa. They have been well studied in livestock of sub-Saharan Africa, but poorly studied in companion animals. Given their socioeconomic importance, the African Small Companion Animal Network (AFSCAN), as part of the WSAVA Foundation, initiated a standardized multi-country surveillance study. Methods: In six countries (Ghana, Kenya, Nigeria,Tanzania, Uganda, and Namibia) in both rural and urban settings, 160 infested cats were sampled to assess their ectoparasite community (ticks and fleas), as well as the micro-parasite prevalence within those ectoparasites (60 and 118 pools of ticks and fleas, respectively) and blood (276 cats, including 116 non-infested). Results: Almost two thirds of all infested cats originated from Tanzania and Kenya. Despite the large macro-geographical variation, no consistent difference was found in ectoparasite diversity and numbers between East and West Africa. Far more flea-infested than tick-infested cats were found. The most dominant ectoparasite was Ctenocephalides felis. Among the ticks, the exophilic Haemaphysalis spp. were the commonest, including species that are not typically linked with companion animals (Haemaphysalis spinulosa and Haemaphysalis elliptica). The most prevalent pathogens found in the blood and fleas were Bartonella henselae and Mycoplasma haemofelis. In the ticks, the dog-associated Hepatozoon canis was most commonly found. A high degree of co-parasitism was found in all countries and habitats. Conclusions: Our continent-wide standardized field study highlights the cat's potential to serve as a reservoir of pathogens that can be transmitted to humans or livestock, especially when cats are expected to become more commonly kept in African villages and towns.
Keywords: Cat; Sub-Saharan Africa; Ticks; Fleas; Vector-borne pathogens; xodes; Haemaphysalis; Rhipicephalus; Amblyomma; Ctenocephalides